Assessing the Macroeconomic Implications of Climate Change On Indian Economy - Mukesh Kumar Mishra (ZBW - Leibniz Information Centre for Economics, 2023)
This paper aims to assess the macroeconomic implications of climate change on the overall Indian economy, considering various sectors and key macroeconomic indicators. It examines the impact of climate change on GDP growth, employment, inflation, fiscal policy, trade, and other relevant factors. The study utilizes empirical data, economic models, and policy analysis to provide insights into the potential risks and opportunities arising from climate change in India. Furthermore, it explores policy interventions and adaptation strategies that can mitigate the adverse effects and enhance the resilience of the Indian economy in the face of climate change. To address this challenge, the policy maker must take urgent action by increasing funding commitments for sustainable Economic Growth, improving effectiveness, encouraging private sector involvement, strengthening capacity building, promoting innovation and technology transfer, Inflations and prices, Green Investment and capital flows, enhancing domestic resource mobilisation, and fostering international trade and distribution effects. Understanding the macroeconomics of climate change is crucial for policymakers, businesses, and societies to develop effective strategies for mitigating greenhouse gas emissions, adapting to the changing climate, and promoting sustainable economic development. It involves assessing the costs and benefits of different policy measures and considering the long-term implications for Indian economic stability and welfare. Overall, addressing these new and multiple shocks requires a comprehensive and holistic approach that takes into account the interconnections between different sectors, regions, and global challenges.
Keywords: E5; E6; Q5; F1; 330; Macroeconomics; Climate Change; Green Growth; International Trade